Antioxidant Activities and Allelopathic Potential of Chonemorpha splendens Chun et Tsiang Stem Methanol Extract. Issue 4 (8th March 2022) - Fu, Jiantao; Zhao, Xu; Wang, Lanying; Zhang, Yunfei; Luo, Yanping
Abstract: Finding agriculturally active compounds from nature or finding active lead compounds from natural products, artificial synthesis and structural modification are the main ways to create new agrochemical. In order to explore the agricultural activities of Chonemorpha splendens Chun et Tsiang ( C. splendens ), an important medicinal plant, the antioxidant activities and allelopathic potential were investigated. C. splendens was extracted with methanol, then, C. splendens methanol extract (CSME) were extracted with petroleum ether, chloroform, ethyl acetate and butanol. Reducing activity, lipid peroxidation, and the scavenging abilities for DPPH⋅, O2 −., HO⋅, and H2 O2 were also measured and allelopathic potentials were evaluated by bioassay method. GC/MS analysis revealed that esters were the main component (66.34 %) of CSME, the total CSME flavonoid content was 313 mg g −1 (rutin equivalent). The chloroform phase of CSME was identified as stigmasterol by NMR for the first time. The DPPH⋅ scavenging rate of CSME was 87 %, with an IC50 value of 0.12±0.02 mg mL −1, which was significantly difference from the positive control, Trolox. Chloroform fraction showed the strongest inhibitory effect against Mimosa pudica (MP) seed germination at 1.0 mg mL −1 (100 % inhibition), which was better than that of the chemical herbicide paraquat. In the seed growth experiment, systematic EC50 and the principal component analysis (PCA) were used to assess the allelopathic potential of extracts. The systematic EC50 values of Crotalaria pallida Ait. (CP), Bidens pilosa L. (BP) were significantly greater than MP. MP, Oryza sativa L. (OS) and Lactuca satiua L., (LS) inhibited all parameters. Our results would provide an idea for controlling weeds through allelopathy from C. splendens to reduce dependency on synthetic herbicides. Abstract :